Professional vision of classroom management and learning support in science classrooms: Does professional vision differ across general and content-specific classroom interactions? - Steffensky, Mirjam; Gold, Bernadette; Holodynski, Manfred; Möller, Kornelia (International journal of science and mathematics education, 2015)
The present study investigates the internal structure of professional vision of in-service teachers and student teachers with respect to classroom management and learning support in primary science lessons. Classroom management (including monitoring, managing momentum, and rules and routines) and learning support (including cognitive activation and structuring of content) are important dimensions of instructional quality. While classroom management is considered as a mainly noncontent-specific aspect of instructional quality, learning support in science classrooms is content-specific. The aim of the current study was to investigate whether professional vision is a general ability of teachers, or a two-dimensional ability which depends on the specific focus of instructional quality considered. In a sample of both 241 German student teachers from different universities and in-service teachers from primary science classes, two video-based instruments were used for assessing professional vision of classroom management and professional vision of learning support. A structural equation model revealed a two-dimensional structure with a high correlation between professional vision of classroom management and of learning support. (Orig.).